The Ukrainian Vertep – Nativity Performance: On the Question of Incorporating the Christmas / Koliada Celebrations into the National Register of Intangible Cultural Heritage of Ukraine - Sendetskyy, Andriy (Ethnologies, 2023)
In this article I review the current status and forms of the Ukrainian vertep (вертеп, nativity performance). The overview is based on my field recordings and historical materials of numerous researchers. I use historical and comparative approaches. Three traditional forms of vertep are practiced today in Ukraine: a dramatic skit of a theatrical group of actors; a choral performance of Christmas and New Year’s carols with a “Bethlehem star”; and a representative nativity scene with a cave or manger called betleiem or shopka, featuring puppet figures of biblical characters. Depending on the form of the performance and the ethnographic region, a variety of scenarios, carol repertoire, and characters can be seen in vertep presentations. This folk-artistic tribute to Christmas in Ukrainian culture merits retention, safeguarding, study, and popularization in the world as an element of intangible cultural heritage.